Cone beam computed tomography and image registration based on target area for stereotactic body radiation therapy of lung cancer. Issue 1 (December 2021) - Gui, Long-Gang; Shi, Miao; Li, Jun
ABSTRACT: This paper aims to compare the dosimetric parameters of the original plan and the simulated plan to explore the clinical value of cone beam CT and planned CT image registration based on the target area. The results showed that Dmax, Dmin, dmean and V60 of PTV in the original plan were (108.3 ± 1.1)%, (97.2 ± 0.3)%, (102.6 ± 0.6)% and (95.2 ± 0.6)% respectively. The Dmax of spinal cord was (9.6 ± 1.8) gy, the V20 of lung was (5.2 ± 1.9)%, and the dmean of lung was (− 3.7 ± 1.5) gy; however, when the target area was translated in the three directions of the patient's back, right side and foot, the dosimetric parameters of the target area (Dmax, Dmin and V60), dmean and V20 of lung and Dmax of spinal cord showed slight differences, which all met the limit requirements of target area and dangerous organs (OARs) (RTOG) 0915 report. Therefore, target based image registration is feasible. If the registration translation error is less than or equal to 1 cm, there is no need to re move the treatment bed according to the registration error.